Influence of e-government on organization communication performance: A case of Morogoro regional commissioner’s office - Shemsanga, Zidikheri M (Mzumbe University, 2024)
Dissertation submitted to the School of Public Administration and Management in partial fulfillment of the requirements for the award of degree of Masters of Science in Human Resource Management (MSc. HRM) of Mzumbe University.